SOSIALISASI DAN PELATIHAN PEMBUATAN HANDSANITIZER ALAMI KEPADA KELOMPOK PEMUDA GEREJA - Marulam MT Simarmata (Universitas, 2021)
The COVID-19 virus in Indonesia has infected more than 1,600 people, and has caused around two hundreds of deaths in Indonesia and is predicted to continue to grow. The panic that has arisen is the alleged lack of socialization and education in the community. Students who have been equipped with an understanding and logical way of thinking, are felt to be present to contribute ideas to community groups in the form of socialization and training in making natural handsanitizers. The purpose of this activity is to provide training to the youth of the GKPS church Jl. Jend Sudirman Pematangsiantar on how to make a natural handsanitizer which will then be distributed to the congregation. The members of the church youth who participated in thistraining were quite enthusiastic. Thisindicatesthe desire to increase youth's selfability to improve performance as well as self-competence for entrepreneurship. Theresults of the training in products will be distributed to the congregation. In additionto these objectives, this activity is expected to generate sensitivity and desire to dobusiness among young people, and show the existence of Simalungun University students in responding to the COVID-19 pandemic.